PRECEPTOR MENTOR TRAINING FOR MIDWIVES - Panselina Widowati, Lorensia; Suhaid, Dewi Novitasari; Leoni Irawan, Yetty; Margaretha Manungkalit, Eviyani; Kartiko Kusumo Wardani, Dyah Woro; Suci Dwi Aningsih, Baharika; Ida Pratiwi, Agustina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Midwifery education programme is an educational forum that graduate professionals to support women throughout their life cycle, using the paradigm that the process women experience is a natural thing. Efforts must be made to improve midwive students' competencies through hands-on learning using the preceptorship method. The preceptorship is a form of clinical learning that helps students to be better prepared for organizational and professional structures and to become more productive. A preceptor's role is to provide support, supervision, monitor learning and assess student placements. Effective Preceptorship can be carried out by preparing Preceptors through an understanding of the duties, responsibilities and use of methods in accompanying students in clinics. Therefore, training is needed to improve the competency of supervising midwives as educators and mentors in clinics. The training was conducted online for 2 days. The assessment of competence improvement is carried out according to the method used in the training process, namely audio-visual. The results of the activities are effective and go in the right direction according to the objectives aimed at in the planning.